Comments on "A physical model and constitutive equations for complete characterization of S-N fatigue behavior of metals". (May 2017) - Wu, Xijia
Abstract: In a recent paper published in Acta Materialia [Ravi Chandran, Acta Materialia 121 (2016) 85–103], the author assumed that crack initiates instantaneously to a size proportional to the applied stress minus the fatigue endurance limit over the range between the fatigue limit and the ultimate strength of the material. However, this relationship has never been proven experimentally. It contradicts to the understanding of fatigue crack nucleation from accumulation of persistent slip bands, which is a process, not an instantaneous event, as supported by numerous experimental observations. Therefore, the proposed S-N curve relationship based on instantaneous "crack initiation" should not be deemed as a "physical model".